Development of Barinjam Learning Media for Algebraic Expression Operations at SMP Negeri 1 Permata Kecubung - Novantoro, Taufik; Putra, Chandra Anugrah; Misyanto, Misyanto; Elhawwa, Tazkiyatunnafs (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2026)
Algebra is a fundamental topic in junior secondary mathematics, yet many Grade VII students experience difficulty because algebraic operations require a transition from concrete arithmetic thinking to abstract symbolic reasoning. This study aimed to develop and validate BARINJAM, or Board Algebra Operations Joyful Activity in Mathematics, as a concrete, low-cost, offline, and culturally contextualized learning medium for algebraic operations at SMP Negeri 1 Permata Kecubung. The study employed a research and development design using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The participants were 33 Grade VII students from classes VII A and VII B, one mathematics teacher, and three expert validators in material, media, and language. Data were collected through expert validation sheets, teacher and student response questionnaires, observation, and documentation. The data were analyzed descriptively by converting validation and response scores into percentages. The results showed that BARINJAM met the feasibility criteria, with material expert validation reaching 100%, media expert validation reaching 80.38%, and language expert validation reaching 100%. The small-scale trial showed a teacher response of 94.73% and a student response of 88%, while the large-scale trial after revision showed an increased teacher response of 98.68% and a student response of 89.24%. These findings indicate that BARINJAM is feasible and practical for supporting Grade VII algebra learning. The media helps represent variables, constants, positive and negative terms, and algebraic operations through concrete manipulation. Further research is needed to examine its effectiveness using complete pretest-posttest data, gain analysis, and statistical testing.